TEACHING ENGLISH BY USING GENERAL METHODS - Temirov, Sirojiddin (Журнал иностранных языков и лингвистики, 2023)
The article presents the various types of methodology of teaching English. Throughout the history of mankind, many different educational methods have been developed.